Violeta went to heaven [videorecording (DVD)]. - Farias, Roberto; Aguilera, Gabriela; Durand, Thomas; Quevedo, Christián; Gavilán, Francisca, 1973-; Tagle, Marcial (Kino Lorber, 2013)
The extraordinary story of the iconic poet, musician and folksinger Violeta Parra, whose songs have become hymns for Chileans and Latin Americans alike. Director Andres Wood traces the intensity and explosive vitality of her life, from humble origins to international fame, her defense of indigenous cultures and devotion to her art.